Reinforced potassium and ammonium storage of the polyimide anode in acetate-based water-in-salt electrolytes - Shen Qiu (Electrochemistry Communications, 2021)
Aqueous K+ and NH4+ ion batteries are emerging as promising alternatives for energy storage; however, the lack of excellent anode materials limits their development. Here we demonstrate a polyimide material as an appealing anode in “water-in-salt” (WiS) electrolytes of potassium acetate and ammonium acetate. Specifically, this anode delivers a high capacity of ~140 mAh g−1, a high rate capability of 200C, and outstanding cycling of 30,000 cycles for K+ storage. Interestingly, it exhibits an even higher capacity of ~160 mAh g−1, a comparable rate capability of 100C, and excellent cycling of 30,000 cycles for NH4+ storage. Such electrochemical performance surpasses that in conventional diluted electrolytes, which highlights the benefits of WiS electrolytes in bolstering ion storage properties.